The dusty aftermath of SN Hunt 248: merger-burst remnant?. Issue 3 (28th September 2017) - Mauerhan, Jon C.; Van Dyk, Schuyler D.; Johansson, Joel; Fox, Ori D.; Filippenko, Alexei V.; Graham, Melissa L.
Abstract: SN Hunt 248 was classified as a non-terminal eruption (a supernova 'impostor') from a directly identified and highly variable cool hypergiant star. The 2014 outburst achieved peak luminosity equivalent to that of the historic eruption of luminous blue variable (LBV) η Car, and exhibited a multipeaked optical light curve which rapidly faded after ∼100 d. We report ultraviolet (UV) through optical observations of SN Hunt 248 with the Hubble Space Telescope (HST) about 1 yr after the outburst, and mid-infrared observations with the Spitzer Space Telescope before the burst and in decline. The HST data reveal a source which is a factor of ∼10 dimmer in apparent brightness than the faintest available measurement of the precursor star. The UV–optical spectral energy distribution (SED) requires a strong Balmer continuum, consistent with a hot B4–B5 photosphere attenuated by grey circumstellar extinction. Substantial mid-infrared excess of the source is consistent with thermal emission from hot dust with a mass of ∼10 −6 –10 −5 M⊙ and a geometric extent which is comparable to the expansion radius of the ejecta from the 2014 event. SED modelling indicates that the dust consists of relatively large grains ( > 0.3 μm), which could be related to the grey circumstellar extinction which we infer for the UV–optical counterpart. Revised analysis of the precursor photometry is also consistent with grey extinction by circumstellar dust, and suggests that the initial mass of the star could be twice as large as previously estimated (nearly ∼ 60 M⊙ ). Re-analysis of the earlier outburst data shows that the peak luminosity and outflow velocity of the eruption are consistent with a trend exhibited by stellar merger candidates, prompting speculation that SN Hunt 248 may also have stemmed from a massive stellar merger or common-envelope ejection.